Reading Creates Digital Bridges: Interactive Online Reading With Students of Information Sciences and Elementary School Pupils in Croatia - Cupar, Drahomira; Hercog, Patricija; Ribarić, Natali (Bobcatsss, 2023)
Many studies (e.g. Bus, van IJzendoorn, & Pellegrini (1995), Meyer et al. (1994), McGee & Schickedanz (2007), van der Wilt, Femke et al. (2019) and DeBruin-Parecki (2009)) showed the importance and lasting benefits of interactive reading aloud from an early age. This paper is exploring possibilities of improving reading comprehension among 4th grade elementary school pupils using interactive online reading. This paper shows successful collaboration between students and teachers of information sciences and an elementary school teacher and her 4th grade pupils. The aim of this paper is to explore how regular interactive online reading sessions can help pupils to further develop their literacy skills: reading comprehension, storytelling, etc. Furthermore, activities included in this project ended with creation of a collaborative digital story/picture book, which helped all participants to better understand the process of online communication between different parts of Croatia. Since the student involved in the process is from a different region and speaks a different dialect than the pupils, storytelling included learning about different dialects. Most activities were carried out using tales that are part of a well-known Croatian book titled Tales of Long Ago (Priče iz davnine) written by Nobel Prize nominee, Ivana Brlić Mažuranić, often dubbed “the Croatian Andersen”. The project was done in five steps: 1. One student retold one tale, Stribor's Forest (Šuma Striborova), in chakavian dialect and made an audio for pupils. 2. Teacher sent the audio to pupils to listen to the tale and discuss unknown dialect-specific words with their parents. 3. Three consecutive online read-aloud sessions followed, with all project participants and with two tales. 4. Pupils retold the tale in their own words, in shtokavian dialect, and made an audio for the students to listen. 5. During the last week, pupils read aloud the original tale to students and teachers in an online session and afterwards retold it in the form of a picture book created collaboratively: each pupil drew one scene from the tale Stribor’s Forest. Picture book was digitized and shared online between the participants. Each step of the project was evaluated by pupils and other participants using Padlet. At the end of the project, pupils gained new knowledge, improved their literacy skills and online communication, enjoyed reading aloud – whether it was their obligatory reading or other stories chosen by them and their teacher. They also learned about Croatian dialects, learned how to collaborate and communicate online and build a collaborative picture book. Students involved in the project had an opportunity to participate in an online collaborative project, create appropriate online learning and teaching materials, and participate in creation and documentation of collaborative online projects. Authors requested and got signed permission from parents for online communication with the pupils and for use of their photos and work for promoting and presenting this project at the BOBCATSSS conference.